Task-based language teaching methods integrated with local wisdom: The impact on students' writing skills - Husain, Balqis; Suhernita, Suhernita; Abasa, Zulhasmi; Djaguna, Fahmi (Univeritas Papua, 2021)
The researcher conducts the study to increase students’ writing skills through TBLT (Task-Based Language Teaching). The subject of this research consists of 32 students in the VIII A class. The objectives of this research are categorized into 2; (1) to find out whether the implementation of the Task-Based Learning method can improve the students’ writing skills, and (2) to find out what kind of writing aspects improve significantly after using Task-Based Learning method. Research design uses pre-test and post-test. Therefore, both groups are given a pre-test, conduct a treatment, then pass a post-test. This research is conducted at eighth grade in 2019/2020 for one month, from August to September 2020. This research shows that after being taught task-based language teaching, students' writing skills, especially in narrative text, improved substantially. It can be analyzed on post-test performance; no one has reached the excellent, good, and fair categories (0 percent). 37.5 percent of students have reached the appropriate category. 65.2 percent of students had failed in the category unless they had handled it for seven meetings. This result is slightly different from the pre-test result. However, only 25 percent of students fall into the decent category, and 75 percent fail. There are no students who are in weak, moderate, decent, and outstanding categories.